(untitled) (Revista Lusófona de Economia e Gestão das Organizações, 2019)
By dissociating personal interest and impartiality utilitarianism stipulates that a fair person is always disinterested. The capacity to be fair implies the renunciation of any personal interest: whoever is impartial has no personal purpose and whoever pursues a particular end is not impartial. However, beyond the fact that the person who chooses in the light of the principle of total or average utility does not have any personal aim, Rawls argues that the depersonalization and disinterest of the impartial observer: a) imply that the ordering of utilities results from the impartial observer’s dictate; b) intensify interindividual discrimination. Against this utilitarian perspective Rawls bases any claim of justice on the individuals’ interests. The CEO compensation illustrates the differences between utilitarian and Rawlsian approaches. Keywords: disinterest; dictate; impartiality; justice; CEO compensation.